THE IMPORTANCE OF EFFECTIVE DECISION-MAKING IN THE PERFORMANCE OF HUMAN RESOURCES IN BUSINESS - Arjant TOPANICA (Prizren Social Science Journal)
All small or large enterprises, private and public, profitable or unprofitable, regardless of field where they operate need to be managed. All organizations, to achieve a goal, engage a number of resources: human, material and financial. In this context, the manager in the work process unites and coordinates all resources to achieve the goal. The manager uses the most adequate forms to face the competition more efficiently, and to be more successful in the market in increasing the organizational objectives. Practices have proven that the decisive factor for the success or failure of a business is the ability or inability of the management team. The responsibility of the manager in our society is decisive not only for the organization but also for the public attitude towards the management for its success and status, for the future of the economic and social system, and the survival of the organization as an independent institution. Decision making refers to a specific act, or a general process. The decision maker must understand that the decision is necessary and must identify a number of reasonable alternatives before selecting one of them. The decision-making process involves understanding and defining the nature of the situation, which requires making decisions, identification of alternatives, selection of alternatives and its implementation. Effective decision making is done when the decision-maker understands the situation that requires making the decision and solving the problem. An effective decision is one that optimizes a number of factors, such as profit, sales, workers' well-being, etc.